Clinical Characteristics and Outcome of Acute on Chronic Liver Failure Patients at Fatmawati General Hospital - Nikko Darnindro; Annela Manurung; Edi Mulyana; Arnold Harahap; Marlina Dewiastuti; Fenandri Fadillah Fedrizal; Mohammad Sadhyo Prabhasworo (The Indonesian Society for Digestive Endoscopy, 2019)
Background: Acute-on-chronic liver failure (ACLF) is a syndrome characterized by acute liver decompensation with extrahepatic organ failure in patients with pre-existing liver disease causing high short-term mortality. A good knowledge about characteristics and diagnostic of ACLF will help us to give proper treatment. The aim of this study is to know the profile and characteristics of ACLF patientMethod: Retrospective study was conducted to find patient with ACLF between January 2017-January 2018 at Fatmawati General Hospital.Results: Ten patients were diagnosed with ACLF. Six patients admitted with a chief complaint: unconscious, 2 of them had hematemesis in the course-of-treatment. Three patients were admitted with abdominal pain, and 1 patient with hematemesis-melena. Seven patients had Hepatitis-B infection. Aspartate-transaminase to platelet-ratio index (APRI) values varied (median 8.1;minimum 2.81-maximum 34.67). Hepatic encephalopathy, ascites, and acute renal failure were found in 90% of patients. Jaundice can be found in all patients, with mean values of bilirubin levels in patients undergoing test for bilirubin level were 18.56 mg/dL (9/10). Coagulation disorders were found in 60% of patients undergoing haemostasis test. Four patients were diagnosed with grade 3 ACLF. All ACLF patients eventually died during treatment, including third-degree patients who all died within 7 days. Only 2 patients survived more than 7 days, and 4 patients died within 3 days of treatment. Conclusion: mortality rates of ACLF were very high, and are often found in patients with advanced liver disease characterized by high APRI values. The prognosis is related to the number of organ failures. Central nervous system, kidneys and liver are the organs that are often impaired. Because the current treatment method is still limited, further research is needed, especially on biomarkers for better prevention, diagnosis and treatment.